Rancang Bangun Periklanan Berbasis Web Pada Dinas Pendapatan Dan Pengelolaan Keuangan Kota Surabaya - Bia Ardy Permana; Mochammad Arifin; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: Department of revenue and financial management is a place for a company or organization to perform licensing the installation of billboards . Each billboard that has been given permission and posted by the Department of revenue and financial management have a status update. The current system for status of the billboard still require operator assistance so that it allows for some error in update the status of any billboard. Researcher provide solutions for Department of revenue and financial management through the advertising monitoring applications. By using this application the Department of revenue and financial management can monitor and obtain reports on the condition or status of the current advertisement and also through reports generated by applications that can facilitate the process of the registration section, determination section and data collection section. Besides being able to display the status of each advertisement, the application can perform calculations automatically advertisement tax number and validation process that is used to help each section to perform the filter on taxpayers who are less worthy. The results of the evaluation applications for users who have been tested on 8 respondents indicate the number of respondents who say that this application is in accordance with the needs and wishes of users is equal to 92 % .